Characterising convinced sustainable food consumers - Marie von Meyer-Höfer; Vera von der Wense; Achim Spiller (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2013)
The objective of this article is to identify the distinguishing socio-demographic and psychographic features of convinced sustainable consumers in contrast to convinced conventional consumers. Furthermore, it contributes to the sparse literature about tea consumption. This study is based on data collected via an online consumer survey. First respondents took part in a choice experiment with tea varying in its price (four levels) and quality (conventional / organic / fair trade / organic & fair trade). Then they had to complete a questionnaire about their attitudes towards food consumption. Respondents, who always chose sustainable tea, at no matter what price, were grouped and those that always chose the conventional tea. T-Tests and bivariate logistic regression are used to analyse the influencing socio-demographic and attitudinal dimensions that characterise the two groups of convinced consumers. Convinced sustainable consumers are more often female than male and perceive that their personal purchase decision has an impact on overall sustainable development. They show a higher willingness to increase sustainability through their consumption behaviour. They are very much interested in high food quality and are not as much influenced by advertisements and offers in their purchase decision-making as convinced conventional consumers. The main contribution of this study is to provide practical information for actors in the field of sustainable food marketing about how to target their most relevant segment, the convinced sustainable consumer.
Keywords: Q13; Q18; 330; sustainable food consumption; convinced consumers; heavy buyers; tea consumption